Service specification in pre-tender phase of public procurement - A triadic model of meaningful involvement. Issue 1 (January 2020) - Holma, Anne-Maria; Vesalainen, Jukka; Söderman, Anne; Sammalmaa, Johanna
Abstract: The purpose of this research is to define the actor roles and collaborative practices that are central to service specification co-development in relation to the pre-tender phase of public procurement. We propose a new model of meaningful stakeholder involvement in the context of public service specification as a triadic setting. In addition to the theoretical value, the proposed model guides public procurement units on how to define their roles as intermediaries and to design a service specification process involving internal customers and providers of a service. The approach adopted highlights the meaningfulness of involvement by referring to the types of cooperative roles and practices that are both suitable for the situation and well understood and implemented by the cooperative parties. Service specification co-development is defined as a triadic setting involving buyers, service providers, and internal customers. This study consists of two longitudinal empirical public procurement cases viewed with the aid of a theoretical framework drawn from the general involvement and public-sector-specific involvement literature. Managerial implications relate to involving stakeholders early in the process, focusing on value creating activities, and sharing relevant information throughout the pre-tender phase. Highlights: A triadic model of meaningful stakeholder involvement to specify public services. Triadic setting involves buyers, service providers, and internal customers. Co-development of the pre-tender phase of public procurement. Cooperative roles and practices that are suitable for complex service procurement. Focus on value creating activities and sharing relevant information.